Levels of heavy metals and their binding protein metallothionein in type 2 diabetics with kidney disease - Raudenska, Martina; Dvorakova, Veronika; Pacal, Lukas; Chalasova, Katarina; Kratochvilova, Monika; Gumulec, Jaromir; Ruttkay-Nedecky, Branislav; Zitka, Ondrej; Kankova, Katerina; Adam, Vojtech; Masarik, Michal (Journal of biochemical and molecular toxicology, 2017)
Hyperglycemia, a major metabolic disturbance present in diabetes, promotes oxidative stress. Activation of antioxidant defense is an important mechanism to prevent cell damage. Levels of heavy metals and their binding proteins can contribute to oxidative stress. Antiradical capacity and levels of metallothionein (MT), metals (zinc and copper), and selected antioxidants (bilirubin, cysteine, and glutathione) were determined in 70 type 2 diabetes mellitus (T2DM) subjects and 80 healthy subjects of Caucasian origin. Single nucleotide polymorphism (rs28366003) in MT gene was detected. Antiradical capacity, conjugated bilirubin, and copper were significantly increased in diabetics, whereas MT and glutathione were decreased. Genotype AA of rs28366003 was associated with higher zinc levels in the diabetic group. The studied parameters were not influenced by renal function. This is the first study comprehensively investigating differences in MT and metals relevant to oxidative stress in T2DM. Ascertained differences indicate increased oxidative stress in T2DM accompanied by abnormalities in non-enzymatic antioxidant defense systems.
Keywords: Oxidative Stress; Polymorphism, Single Nucleotide; oxidační stres; Humans; oxidative stress; Case-Control Studies; genetické asociační studie; lidé středního věku; metallothionein; studie případů a kontrol; Copper; ledviny; jednonukleotidový polymorfismus; Female; Aged; Kidney; Zinc; senioři; lidé; Biomarkers; chronická renální insuficience; zinek; Metallothionein; diabetic kidney disease; Diabetes Mellitus, Type 2; měď; biologické markery; ženské pohlaví; diabetické nefropatie; stupeň závažnosti nemoci; Genetic Association Studies; Male; Middle Aged; Czech Republic; Aged, 80 and over; Diabetic Nephropathies; Severity of Illness Index; diabetes; senioři nad 80 let; metalothionein; Česká republika; mužské pohlaví; Renal Insufficiency, Chronic; diabetes mellitus 2. typu; heavy metals